Publishing Sacrobosco's De sphaera in Early Modern Europe Modes of Material and Scientific Exchange - Valleriani, Matteo; Ottone, Andrea (Springer International Publishing : Imprint: Springer, 2022)
This open access volume focuses on the cultural background of the pivotal transformations of scientific knowledge in the early modern period. It investigates the rich edition history of Johannes de Sacrobosco's Tractatus de sphaera, by far the most widely disseminated textbook on geocentric cosmology, from the unique standpoint of the many printers, publishers, and booksellers who steered this text from manuscript to print culture, and in doing so transformed it into an established platform of scientific learning. The corpus, constituted of 359 different editions featuring Sacrobosco's treatise on cosmology and astronomy printed between 1472 and 1650, represents the scientific European shared knowledge concerned with the cosmological worldview of the early modern period until far after the publication of Copernicus' De revolutionibus orbium coelestium in 1543. The contributions to this volume show how the academic book trade influenced the process of homogenization of scientific knowledge. They also describe the material infrastructure through which such knowledge was disseminated, and thus define the premises for the foundation of modern scientific communities.